(untitled) (Bangladesh Journal of Nuclear Medicine, 2019)
Objectives: Glomerular Filtration Rate (GFR) is an important parameter of kidney function. Many methods are used to measure GFR namely: inulin clearance, double plasma sample method (DPSM), Gates’ method, and equation based method. DPSM has become the gold standard in clinical research. Gates’ method is routinely practiced at National Institute of Nuclear Medicine and Allied Sciences. Chronic kidney disease epidemiology collaboration (CKD-EPI ) equation is encouraged as it is simple and reliable. The aim of the study was assesment of agreement between Gates’ method and CKD-EPI equation with plasma sample method for estimation of GFR. Patients and methods: This cross sectional observational study was carried out at NINMAS, during July 2017 to June 2018. A total of 70 subjects referred for 99mTC-DTPA renography along with GFR estimation, were included in this study. Result: The mean GFR value evaluated by DPSM, Gates’ and CKD-EPI equation were, 81.86 ± 22.42, 86.13 ± 26.70 and 78.48 ± 23.87 mL/min/1.73 m2 respectively. A strong positive correlation (r = 0.922) was found between DPSM and Gates’ method and also between DPSM and CKD-EPI equation (r= 0.930). The Gates’ and CKD-EPI equation also showed strong positive correlation (r = 0.872). The mean difference between DPSM and Gates’, between DPSM and CKD-EPI equation, between Gates’ and CKD-EPI equation were 4.26 ± 10.45, 3.38 ± 8.78 and 7.64 ± 13.09 mL/min/1.73 m2 respectively. Conclusion: Strong positive correlation and excellent agreement were observed between DPSM and Gates’ and also between DPSM and CKD-EPI equation. Strong correlation was also found in between Gates’ and CKD-EPI equation. So, DPSM, Gates’ method and CKD-EPI equation can reflect GFR almost equally and used interchangeably. Bangladesh J. Nuclear Med. 22(1): 36-40, Jan 2019